A Cryptographic based Approach for Data Hiding in Advanced Video Sequences - Dr. Anand Babu J, Vinay D R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Data hiding in video streams became more popular in the present world, since there is a high frequency of data communication over the internet. Hiding the data in video streams provides more security as well as increases embedding capacity than hiding inside the images. The quantity of information to be embedded into the video increases, it can badly influence the video excellence make it inappropriate for certain appliances. The main concerns in data hiding in videos are its high visual excellence, increased hiding capacity, video stream size etc. In this paper, a new data hiding technique is proposed in compressed H.264 Video Streams. At first, the information to be embedded is encrypted using Cryptography approach. The Cryptographic approach helps to encrypt the plain information based on the elliptic points produced by choosing the large prime number. The encrypted data is embedded into the transformed DCT coefficients of I, B and P video frames. The experiment is conducted for different set of video sequences. The results shows that the proposed method yields better performance in terms of Peak signal to noise ratio (PSNR), Structural similarity index (SSIM) and Video quality measure (VQM) when compare to existing methods.